Memória e historiografia no documentário: o fim e o princípio de Eduardo Coutinho - Zanelli, Mirian Luciana Guimarães [UNESP] (2014)
This study discusses about the integration of memories and film in the field of the historians work, in order to affirm the value of oral and audiovisuals sources for the writing of history. We Investigated theoretical and methodological issues we consider the nature and historiographical renovations occurred in the twentieth century allowed others interpretations about the past and allowed researchers to establish new methodological procedures on a variety themes and objects. Here is a reflection on the characteristics of documentaries examining the dialogue that history established with cinema and criticizing the notions that the historians have about the issues of visuality. We evaluated the use of unwritten for historiographical production through the movie O Fim e o Princípio, from Eduardo Coutinho (2005). We based our analysis on the memories and narratives of the characters of the documentary. We understood that the forgetting and remembering part of the same dynamic and that the collective memory is anchored in social settings, but we admit the existence of an individual memory and a sensible intuition that acts spontaneously in our memories.